Membangun Kesadaran Kewarganegaraan Yang Aktif Dan Partisipatif Pada Siswa Sekolah Dasar - laelly, tazkia aisha; febriyanti, utari; apriliani, firda; yanti, novi; sunaryati, titin (Peneliti.net, 2023)
Civic education is an important aspect in building the character of active and participatory citizens. At the elementary school level, civic education has a crucial role in shaping active civic awareness in students. Citizenship awareness is an understanding and appreciation of the rights, responsibilities and roles of citizens who contribute to building a better society. Students' active participation in civic activities will shape attitudes, values and skills that are essential for their future as responsible members of society. In this study, we analyze civic education in primary schools to understand how civic education builds active and participatory civic awareness in students. The benefits of this research are as a reference for what civic education has an important role in shaping students' attitudes, knowledge, and skills in terms of active and participatory citizenship in shaping a generation that is more involved in community life. The purpose of the study is to analyze civic education in primary schools with a focus on efforts to build active and participatory citizenship awareness in primary school students. The method used in this research is qualitative method, a research approach used to understand and explain human phenomena in their natural context. The result of this research is to build active and participatory citizenship awareness in elementary school students has a very positive long-term effect on individuals and society as a whole. It helps create citizens who are aware of their rights and responsibilities in building a just, democratic and sustainable society.